2017
DOI: 10.1002/brb3.738
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cerebellar structure and emotional memory in depression

Abstract: BackgroundA few studies have been conducted on the relationship between cerebellar volume and emotional memory or clinical severity in major depressive disorder (MDD). In this study, we aimed to compare the volume and density of the cerebellar gray matter (GM) in patients with MDD and in healthy controls (HCs) and explore the association between these cerebellar parameters and measurements of emotional memory and clinical severity.MethodVoxel‐based morphometry (VBM) and Individual Brain Atlases using Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 60 publications
4
22
0
Order By: Relevance
“…In line with previous studies (Lai and Wu, 2016 ; Xu L.-Y. et al, 2017 ), we found that some cerebellum regions showed high discriminative powers, such as left cerebellum 7b, right cerebellum 3, vermis 7 and vermis 8, indicating the cerebellum as a key node in the cognitive processing of MDDs (Lu et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies (Lai and Wu, 2016 ; Xu L.-Y. et al, 2017 ), we found that some cerebellum regions showed high discriminative powers, such as left cerebellum 7b, right cerebellum 3, vermis 7 and vermis 8, indicating the cerebellum as a key node in the cognitive processing of MDDs (Lu et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…Functional MRI studies have revealed that the cerebellum is involved in cognition and emotion in addition to motor control 242526. Our findings are in line with previous research showing that emotional memory and the severity of depressive symptoms are associated with structural changes in anterior gray-matter regions of the cerebellum in patients with depression 26…”
Section: Discussionsupporting
confidence: 92%
“…Besides, the activity level in this area was correlated with depressive symptom in the rMDD group, which may imply that the state-related hyperactivities in the anterior lobe of cerebellum found in the rMDD patients are involved in a compensatory mechanism. The relation between cerebellum brain activity and depressive symptom has been reported by fMRI and sMRI findings (Zeng et al, 2012; Xu et al, 2017). This association may be illustrated by the cerebellar connections with limbic regions, brainstem, temporal lobe, prefrontal lobe, and cingulate gyrus, areas shown to have profound influence on cognitive processing and emotional regulation (Haines et al, 1984; Middleton and Strick, 2001; Turner et al, 2007).…”
Section: Discussionmentioning
confidence: 88%